2014
DOI: 10.1111/all.12530
|View full text |Cite
|
Sign up to set email alerts
|

Predictive values of component-specific IgE for the outcome of peanut and hazelnut food challenges in children

Abstract: Ara h 2- and Cor a 14-specific IgE are useful to estimate the probability for a positive challenge outcome in the diagnostic work-up of peanut or hazelnut allergy making some food challenges superfluous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
183
2
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(205 citation statements)
references
References 20 publications
5
183
2
15
Order By: Relevance
“…In contrast, none of the sensitized but peanut-asymptomatic subjects demonstrated specific IgE reactivity to the peanut seed storage proteins Ara h 1, Ara h 2, Ara h 3 and Ara h 6, resulting in specificities of 100% for those allergens. In contrast, recent studies have shown that 26% of sensitized but tolerant patients' sera contained IgE specific to Ara h 2 [19], and that a 95% probability of a positive peanut challenge could only be established for sIgE specific to Ara h 2 with a threshold of 42.2 kU A /l and above [20]. We showed that 72% of Austrian peanut-allergic subjects had IgE specific to at least one of those four allergens.…”
Section: Discussionmentioning
confidence: 52%
“…In contrast, none of the sensitized but peanut-asymptomatic subjects demonstrated specific IgE reactivity to the peanut seed storage proteins Ara h 1, Ara h 2, Ara h 3 and Ara h 6, resulting in specificities of 100% for those allergens. In contrast, recent studies have shown that 26% of sensitized but tolerant patients' sera contained IgE specific to Ara h 2 [19], and that a 95% probability of a positive peanut challenge could only be established for sIgE specific to Ara h 2 with a threshold of 42.2 kU A /l and above [20]. We showed that 72% of Austrian peanut-allergic subjects had IgE specific to at least one of those four allergens.…”
Section: Discussionmentioning
confidence: 52%
“…[4] A recent Japanese study has suggested an Ara h 2 cutoff of 4 kU/L to have a 91% PPV for peanut allergy, [16] and in a German study a 90% probability for positive peanut challenge for Ara h 2 was estimated at 14.4 kU/L. [17] In our population, commonly used PPVs for SPT, ImmunoCAP Peanut and Ara h 2 performed suboptimally at 85%, 77% and 73%, respectively. Furthermore, there were significant ethnic differences, with the Xhosa patients faring even more poorly using these cut-offs.…”
Section: Discussionmentioning
confidence: 60%
“…Forty to sixty percent of children with milk or egg allergy will outgrow their food allergy until the age of 6 years (100, 101), whereas this occurs at a lower rate in children with allergy to peanut or tree nuts. These individuals may be considered prototypic for tolerance acquisition after established potentially life-threatening food allergy (100,(102)(103)(104)(105). The sequence of events and biomarkers that define individuals with persistent food allergy and those who outgrow their food allergy remain unclear.…”
Section: Oral and Sublingual Immunotherapy In Food Allergymentioning
confidence: 99%